利用CRISPR/Cas9慢病毒系统构建肺部EZH2基因敲除小鼠 (Zhongguo Fei Ai Za Zhi, 2018)
BACKGROUND AND OBJECTIVE: It has been proven that CRISPR/Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated 9) system was the modern gene-editing technology through the constitutive expression of nucleases Cas9 in the mammalian, which binds to the specific site in the genome mediated by single-guide RNA (sgRNA) at desired genomic loci. The aim of this study is that the animal model of EZH2 gene knockout was constructed using CRISPR/Cas9 technology. METHODS: In this study, we designed two single-guide RNAs targeting the Exon3 and Exon4 of EZH2 gene. Then, their gene-targeting efficiency were detected by SURVEYOR assay. The lentivirus was perfused into the lungs of mice by using a bronchial tube and detected by immunohistochemistry and qRT-PCR. RESULTS: The experimental results of NIH-3T3 cells verify that the designed sgEZH2 can efficiently effect the cleavage of target DNA by Cas9 in vitro. The immunohistochemistry and qRT-PCR results showed that the EZH2 expression in experimental group was significantly decreased in the mouse lung tissue. CONCLUSION: The study successfully designed two sgRNA which can play a knock-out EZH2 function. An EZH2 knockout animal model was successfully constructed by CRISPR/Cas9 system, and it will be an effective animal model for studying the functions and mechanisms of EZH2.